Molecular Phylogeography and Evolutionary History of the Endemic Species Corydalis hendersonii (Papaveraceae) on the Tibetan Plateau Inferred From Chloroplast DNA and ITS Sequence Variation - Li, Qien; Guo, Xiao; Niu, Junfeng; Duojie, Dongzhu; Li, Xianjia; Opgenoorth, Lars; Zou, Jiabin (Frontiers in Plant Science, 2020)
In response to past climatic changes, the species with different habits or adaptive traits likely have experienced very different evolutionary histories, especially for species that restricted to high mountain areas. In order to trace how Quaternary climatic oscillations affected range distributions and intraspecific divergence of such alpine plants on the Tibetan Plateau, here, we investigated maternally inherited chloroplast DNA (cpDNA) markers and biparentally inherited nuclear ribosomal internal transcribed spacer (ITS) DNA variations and aimed to explore the phylogeographic history of the endemic alpine species Corydalis hendersonii Hemsl. (Papaveraceae). We sequenced four cpDNA fragments (trnS-trnG, trnT-trnL, atpH-atpI and psbE-petL) and also the nuclear (ITS) region in 368 individuals from 30 populations across the species’ range. The network and phylogenetic analysis based on cpDNA variations identified 15 chlorotypes that cluster into three distinct clades. However, our nuclear DNA results demonstrated that there were four genetic/geographical groups within C. hendersonii. Some common and highly divergent cpDNA and ITS haplotypes were distributed in the populations of central and northeastern Tibetan Plateau, and the highest nucleotide diversity and genetic differentiation were detected in the central region. Demographic tests further indicated that the populations of southwestern and western Tibet may have experienced recent range expansion, which most likely occurred during the last glacial maximum (LGM) and continued its expansion after the beginning of the Holocene. These two different groups of this species may have derived from potential refugia that existed in the central and/or northeastern regions of Tibet during recent interglacial periods. In addition, our AMOVA analyses detected high genetic differentiation along with the whole sampling range. Also, distinct phylogeographic structures were detected among populations of C. hendersonii based on both of cpDNA and ITS variation. These findings shed new light on the importance of climatic oscillations during Quaternary and complex local topography as causes of intraspecific diversification and demographic changes within cold-tolerant herbs in the Tibetan Plateau biodiversity hotspot.